Evaluation of health conditions of elderly patients with osteoarthritis in a city of the interior of Rio Grande do Sul - Juliana Secchi Batista; Daniele Pedott; Lia Mara Wibelinger (Universidade de Fortaleza, 2012)
Objective: To characterize the prevalence of osteoarthritis among the elderly in the city of Passo Fundo - RS, Brazil. Methods: This was an epidemiological cross-sectional study of descriptive and analytical nature, in which a sociodemographic and clinical questionnaire, containing open and closed questions, was applied to subjects aged sixty or over and the data was analyzed using the statistical package SPSS version 18.0. We interviewed 51 elderly patients with knee osteoarthritis, in the period from March 05 to August 05 2011. Results: Most patients were female (n=45, 88.2%), aged 60-69 years (n=22, 43.1%). Regarding education, 13 (25.4%) of the subjects had completed high school, individual monthly income of a minimum wage (n=22, 43%), were nonsmokers (n=49, 96%) and not alcoholics (n=47, 92%). Moreover, 44 (86%) of them reported having some disease, hypertension as the most prevalent (n=21, 41%) and 44 (78.4%) were taking medicine. Concerning the practice of physical activity, more than half of respondents practiced some physical activity (n=41, 80.4%) and attended and elderly group (n=38, 74.5%); also, the vast majority of elderly had taken no fall during the last 06 months (n=41, 80.3%) and considered their health as good (n=28, 56.6%). Conclusions: It may be noted that the socioeconomic and health conditions of the elderly were found to be favorable, but it is worth emphasizing the importance of planning public policies targeting specific needs of the elderly, along with other studies for increasing knowledge about this population.